Penerimaan Audiens Pria Terhadap Soft Masculinity Dalam Videoklip NCT Dream – Candy - Jhosua Audison Siagian; Windri Saifudin (PADARINGAN (Jurnal Pendidikan Sosiologi Antropologi), 2025)
The concept of soft masculinity presents a new dimension of male masculinity with feminine characteristics, often associated with women. This research examines the phenomenon of soft masculinity in the music video Candy by NCT Dream. The music video represents a different concept of masculinity compared to traditional masculinity, showcasing male characters with delicate gestures and various attributes typically associated with women. For adherents of traditional masculinity, such as those in Indonesian society, this is often perceived as a violation of social norms. The Candy music video, as a medium of communication and entertainment, is considered capable of influencing the cognitive, affective, and behavioral aspects of society in accepting this unconventional portrayal of masculinity. Through a qualitative approach using Stuart Hall's reception analysis method, this study focuses on the reception of male NCT Dream fans toward this new cultural phenomenon. The findings indicate that informants who accept soft masculinity in their daily lives are influenced by their cultural and social environment, particularly regarding exposure to K-Pop culture. Meanwhile, rejection of the message adaptation is largely driven by the entrenched social norms within society, requiring men to negotiate the meaning of the message or even reject it outright